The Problems Of Tradition And Innovation In The Armenian Poetry Of The 1960s–1970s - Zakaryan, Hripsime (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
In the 1960s and 1970s, the social–political and literary–cultural life of our country entered a new orbit. A new literary generation came to the scene, which will adjust the main directions of the development of Armenian poetry, orientation standards, content and forms of expression. It seems that the innovative young poets who came to the scene, proposing harmonious ideals and ideas for the new time, were pushed out of the national spheres, but in fact, it is moving towards the origins of the national culture, towards the rich deposits of Armenian medieval poetry. Thus, discussions of national-traditional topics also become relevant. By balancing the past with the new times, it becomes a unique panorama to depict the present with the most pronounced shadow lines. Especially in the 1980s, the traditions of the Armenian Middle Ages had a wide circulation in various types of literature, particularly in poetry, which meant a return to the origins of folk creativity. They can be considered the innovators who reformed, combined and crossed the ancient genres of Armenians: sharakan, taghi, prayer, mythological myths, etc. They tend to the generality of art, which was specific to Armenian medieval art manifested in the form of symbolic universality. The past is represented not by the balance of historical material, but by the present–day interpretation of the internal charges of ideological and philosophical orientations, ancient Armenian traditions, myths, Christian motifs, plots, and images contained in them. However, it should also be noted that this tendency (return to the origins) is generally of a global nature.
Keywords: Philology